Evaluation of siso-ofdm and mimo-ofdm channel's performance using experiment set up and simulations - Abdullahi, Salami Ifedapo (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Interference is an inevitable signal disruption in a wireless communication system. A high level of interference effect (Bit Error Rate (BER)) is experienced mostly in crowded urban areas and indoor environments. Interference caused by Additive White Gaussian Noise (AWGN), Rician and Rayleigh fading reduces the travelled distance and signal level. Additionally, systems employing single modulation techniques and antenna are more likely to be affected by interference. This is because they are incapable of adapting to the environment changes. As such, this research has proposed to evaluate a Single Input Single Output (SISO) Orthogonal Frequency Division Multiplexing (OFDM) capability in an indoor environment as well as apply adaptive modulation techniques and antenna diversity in a simulation experiment to mitigate interference-effect. The first objective of this research is to evaluate the SISO-OFDM channel's performance in an indoor environment against the cleanroom environment, acquired using an experimental setup. The second objective is to ascertain the improvement of SISO-OFDM channel performance when variable modulations are deployed, using the GNU Radio software platform. The third objective is to identify the channel performance's improvement when Multiple Input Multiple Output (MIMO)-OFDM System is deployed using the GNU Radio software. The performance's parameters assessed are the BER and Received Signal Strength Indicator (RSSI) in the case of the empirical testbed. Whereas, for the software simulation implementation, the parameter assessed is the BER. The methodologies adopted in the empirical study involved using SISO-OFDM with the Universal Software Radio Peripheral (USRP) hardware setup to conduct experiments in the laboratory and anechoic chamber environments. The distances between the transmitter and receiver were varied, and the collected measurements were compiled and recorded. The simulation experiment employing the SISO-OFDM system was carried out over various channel conditions, namely AWGN, Rician, and Rayleigh. The MIMO-OFDM system was simulated over different channel conditions, and the performance measurements were compared with that of the SISO-OFDM system. The most important research findings from the empirical study are the ability to identify the interference level at a specific site using the USRP. Based on the findings from the second objective, adaptive modulation can be said to mitigate the interference effect (BER) in a SISO-OFDM system. The key discovery found in the third objective is that the MIMO-OFDM system significantly reduces the interference effect (BER) level usually experienced over a multipath fading channel of a SISO-OFDM system. The major contribution of this research is the capability to share the method to identify interference level at a specific site using a standard radio frequency equipment with the USRP. Moreover, this research is one of the first to assess wireless channel performance in the anechoic chamber using the USRP N210 Software Defined Radio (SDR).